Pengembangan Wisata Gastronomi Pada Destinasi Wisata di Kampung Pathuk Yogyakarta - Vironika Agustin Saputra; Nadya Putri Chandraningtyas; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
Kampung Pathuk Yogyakarta offers several opportunities to be explored and developed. This city is known as the center of Bakpia, special souvenirs from the special region of Yogyakarta. The rapid development of the tourism industry is an opportunity for traditional food to develop further in meeting the daily needs of the community, especially tourists. Community-based tourism is tourism development that involves the local community strongly and can consider social and environmental aspects. Understanding the importance of local wisdom, especially in traditional culinary which is part of tourism development in the special area of Yogyakarta. Traditional food in Yogyakarta is currently very popular among tourists from various regions who can find a variety of Yogyakarta specialties. The research method used is a qualitative method. A literature search was carried out. The results of the study concluded that the Bakpia Pathuk production process has unique potential so that it becomes a potential gastronomic tourism destination.